SISTEM MONITORING PENDAKI GUNUNG SEMERU (SIMPANSE) - Noven Indra Prasetya; Indo Baruna (Melek IT : Information Technology Journal, 2022)
Mount Semeru or Semeru is the highest mountain on the island of Java with a height of 3,676 meters above sea level. Because of its natural beauty and height, Semeru is included in the category of popular tourist objects in East Java, which causes many climbers and nature lovers to visit for climbing. Before climbing, climbers are required to register at the permit post with the aim that officers know the schedule for the end of the climber to climb. If the climber passes the final schedule of climbing, then the climber is required to pay a fine and if the climber for two days does not report to the officer, then the climber's status is considered a lost climber. So far, the data collection process is done manually using the available forms, officers will be very troubled when they have to monitor the schedules of many climbers one by one. Therefore the Mount Semeru Climber Monitoring System or abbreviated SIMPANSE is a solution to overcome problems with licensing officers because of the notification facility on the system that can provide information when there are climbers who exceed the climbing schedule. Based on the test results with several scenarios made, this system is able to fulfill 95% of all scenarios well, so the research can be said to have succeeded in meeting the problems that occurred in the officers at the Semeru licensing post.